Fine tuning of pyridinium-functionalized dibenzo[a, c]phenazine near-infrared AIE fluorescent biosensors for the detection of lipopolysaccharide, bacterial imaging and photodynamic antibacterial therapy. Issue 40 (3rd October 2019) - Liu, Xianglong; Yang, Zhicheng; Xu, Weibo; Chu, Yanmeng; Yang, Ji; Yan, Yongchao; Hu, Yue; Wang, Yu; Hua, Jianli
Abstract : A series of NIR fluorescent probes of dibenzophenazine pyridine salt with different alkyl chain were developed for the detection of LPS. BD2C with ethyl chain exhibited a significant improvement of the singlet oxygen yield and antibacterial property. Abstract : Fluorescent biosensors with aggregation-induced emission (AIE) have received much attention in the field of bioimaging and therapeutic applications. Although the side chains of AIE sensors have important impacts on the optical performance, imaging and therapy, only a few studies were emphasized on side chain effects compared to the well-established fluorescent backbone systems. In this work, a series of turn-on near-infrared (NIR) pyridinium-functionalized dibenzo[ a, c ]phenazine salt fluorescent probes (BD2C /BD8C /BD16C ) possessing ethyl, octyl and hexadecyl chains were designed and facilely synthesized, and the influence of the alkyl chain length on their optical properties, lipopolysaccharide (LPS) detection and singlet-oxygen quantum yield were systematically investigated. The homologs can exhibit both promising AIE properties and desirable large Stokes shift ( ca. 190 nm). Owing to the electrostatic interactions between the two oppositely charged species, the probe with pyridine salt of positive charge could efficiently aggregate with the negatively charged LPS. By reducing the alkyl chain length, BD2C toward LPS showed significant fluorescence enhancement with a relatively low detection limit (2.6 × 10 −8 M). Additionally, the singlet oxygen yield of BD2C also showed a significant improvement (70.6%) compared to BD8C and BD16C (30.7% and 30.2%, respectively). The amphiphilic BD2C bearing ethyl chain and positively charged pyridinium salt can embed into the bacterial membrane, thus increasing the membrane permeability and causing dark toxicity. Furthermore, BD2C can also serve as an effective antibacterial photosensitizer under 530 nm light irradiation by inducing reactive oxygen species (ROS) generation which is a rarely reported example to date.